A Novel Androgen-Induced lncRNA FAM83H-AS1 Promotes Prostate Cancer Progression via the miR-15a/CCNE2 Axis - Liu, Bo; Qian, Duocheng; Zhou, Weidong; Jiang, Huiyang; Xiang, Zhendong; Wu, Denglong (Frontiers in Oncology, 2021)
Prostate cancer (PCa) is one of the most common types of tumors among males worldwide. However, the roles of long noncoding RNAs (lncRNAs) in PCa remain unclear. This study shows that lncRNA FAM83H-AS1 is upregulated in prostate adenocarcinoma, bladder urothelial carcinoma, and kidney renal papillary cell carcinoma samples. Androgen receptor (AR) signaling plays the most important role in PCa tumorigenesis and development. In this study, the results validate that AR signaling is involved in upregulating FAM83H-AS1 expression in PCa cells. Loss-of-function assays demonstrate that FAM83H-AS1 acts as an oncogene in PCa by modulating cell proliferation, cell cycle, and migration. Bioinformatics analysis demonstrates that FAM83H-AS1 is remarkably related to the regulation of the cell cycle and DNA replication through affecting multiple regulators related to these pathways, such as CCNE2. Mechanically, we found that FAM83H-AS1 plays its roles through sponging miR-15a to promote CCNE2 expression. These findings indicate that FAM83H-AS1 is a novel diagnostic and therapeutic marker for PCa.